Implementation of the Project Based Learning (PjBL) Model in Improving the Ability to Understand the Qur'an in the Independent Curriculum at MTsN 4 Tanah Datar - Sari, Nelfa; Tanjung, Alwin (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to analyze and describe the application of the Project Based Learning (PjBL) model to improve the ability to understand the Qur'an in the Merdeka curriculum. This study uses a qualitative approach with a case study type and a single case study type. This study was located at MTsN 4 Tanah Datar. Data were collected through participatory observation techniques, in-depth interviews and documentation studies. Data were analyzed using an analysis model developed by Miles, Huberman and Saldana. The implementation of project-based learning models can improve students' reading skills, especially in terms of tajwid and reading fluency. Project-based learning models are implemented by directing students to construct their own knowledge and understanding in understanding the Qur'an. Students' abilities in understanding the Qur'an, starting from understanding verse by verse, word by word, to the ability to understand the content of the interpretation of a verse and letter, can be improved because students implement it directly in a project. So that in the end, project-based learning models can be used to improve students' abilities in understanding the Qur'an, as evidenced by the increasing understanding of students regarding several verses taught in the Qur'an and Hadith subjects in the independent curriculum. The ability of students to understand the Qur'an, starting from understanding verse by verse, word by word, to the ability to understand lessons that can be absorbed can be improved by implementing a project-based learning model, but still under the supervision and direction of the facilitator.